Between \"Angels and Demons\": trauma in fictional representations of Roger Casement - Bolfarine, Mariana (2015)
The life of the controversial Irish nationalist Roger David Casement, who was sentenced to death for high treason by the British Crown, has inspired writers to produce works of various literary genres: prose, poetry, drama and critical essays. This doctoral dissertation aims to investigate, under the light of trauma theory as suggested chiefly, but not solely by Cathy Caruth, Ron Eyerman and Dominick La Capra, the ways in which the figure of Roger Casement can be associated with traumatic events that have sealed Anglo-Irish relations. Thus, I have selected works that deal with Casements Life as he acts both for and against the trauma inflicted by imperialism respectively as a Victorian hero in Arthur Conan Doyles The Lost World (1912) and as an oblique presence in the 1916 Easter Rebellion in Jamie ONeills At Swim, Two Boys (2001); the trauma surrounding his Trial and the discovery of the homosexual Black Diaries that culminated in his hanging through his representation as a whole man in Mario Vargas Llosas The Dream of the Celt and in Patrick Masons The Dreaming of Roger Casement (2010); and finally, the trauma that persists unresolved in his Afterlife, as a ghost in David Rudkins Cries from Casement as his Bones are Brought to Dublin and as traumatic memory in the Annabel Davis-Goffs The Foxs Walk. As a result, we have found that the representation of Roger Casement in these works, although in various ways, is a metaphor for the traumatic process itself: an embodiment of the disjunction of temporality, [and] the surfacing of the past in the presente (Whitehead) as his presence continues to haunt the story of the transatlantic world.